The Impact of Using Instagram and Whatsapp Social Media on the Intensity of Learning Arabic Language/ تأثير استخدام وسائل التواصل الإجتماعي إنستغرام و واتساب على حافز تعلم اللغة العربية - Amirullah, Nur Ikhsan (UIN Raden Mas Said Surakarta, 2021)
The objectives of the study in this topic is to find out the motivation of students’ learning of the Arabic language in the experimental study and the control study and to find out the effect of using social media Instagram as a learning media on motivating students in the eighth-graders in Islamic Junior High School 6 Sragen to learn Arabic. This study is an experimental study method quantitative method. The method of data collection used is questionnaires. The media used is Instagram. The method of analysis used is paired sample T-test and independent sample T-test. The use of the Instagram learning media has a positive effect on stimulating learning, and this is required by the presence of the change in the paired sample T-test, and the significance score was less than 0,05 (P = 0,001 < 0,05). Then there are significant differences in the scores of the experimental class and the control class students. It can be demonstrated by the independent T-test result (post-test) that the calculated T value (2,539 > 1,999) and the significance score is less than 0,05 (P = 0,000 < 0,05).